The Influence Of Drill And Power Arm Training On Lob And Smash Results In Beginners Athletes PB Kaisar Tegal - irsya, irsya musytafizur ziqri (Journal of Physical Education and Sports, 2024)
This research aims to determine: 1) Whether or not there is an influence of the drill method and arm power on the accuracy of the lob shot. (2) Whether or not there is an influence of drill and arm power training methods on the accuracy of smash hits. (3) Whether there is a difference in the influence of mixed drill and separate drill training methods on the accuracy of lob and smash shots.(4) Whether there is a difference in the influence of athletes who have high arm power and low arm power on the accuracy of lob and smash shots. (5) Whether or not there is a significant interaction between drill training and arm power on the accuracy of lob and smash shots. This research uses a 2 x 2 factorial design.The sample consisted of 20 athletes, the sampling technique used probability sampling, the subjects had been determined, namely 12-15 years old (beginners). The arm muscle power instrument uses the Overhead Medicine Ball Throw test (Widiastuti, 2017: 123) to group subjects and the lob and smash accuracy test instrument uses theory (Frank M. Verducci in Sapta Kunta Purnama, 2010). The data analysis technique used is MANCOVA two track. Research results: (1) There is an influence of drill and arm power training methods on the accuracy of lob shots. Athletes who have high arm power are better trained using mixed drill methods, while athletes who have low arm power are better trained using separate drills. (2) There is an influence of drill training methods and arm power on the accuracy of smash shots. Athletes who have high arm power are better trained using mixed drill methods, while athletes who have low arm power are better trained using separate drills.(3) There is a difference in the influence of mixed drill and separate drill training methods, the significance value is 0.000 < 0.5. This means that there is a significant difference in the influence of the mixed drilling training method and the separate drilling training method. (4) There is a difference in the influence of athletes who have high arm power and low arm power with a significance value of 0.000 < 0.5. This means that there is a significant difference in the influence of athletes who have high arm power and low arm power.(5) There is a significant interaction between drill training and arm power on the accuracy of lob and smash shots, significance value 0.000 < 0.5. This means that there is an interaction between the drill method and arm power on the accuracy of lob and smash shots by novice athletes at PB Kaisar Tegal, which has been proven.